Stock Price Determinant of PT Timah Tbk During the Covid-19 Pandemic - Vinola Christiani; Clara Annicha; Elvin Wiranata; Ari Agung Nugroho (Garuda Prestasi Nusantara Consulting, 2021)
Stock Price Determinant of PT Timah Tbk during the Covid-19 Pandemic, the Covid-19 Pandemic involves the world economy. Lockdown and Large-Scale Social Restrictions make the economy slow down due to the restricted activities. The prices of crude oil and metal commodities also corrected, including the price of tin commodity due to the decrease of demand. Therefore, the aim of this study is to analyze the impact of the tin price variable, Interest Rate (BI Rate), Net Profit Margin (NPM), and Debt to Equity Ratio (DER) on the Stock Price of PT Timah Tbk during the Covid-19 pandemic. This study used a quantitative method. The object of the study was PT Timah Tbk. The samples used were secondary data, which were tin commodity price, and interest rate of SBI in 2020, and the quarterly financial statements of PT Timah Tbk. The analysis method used was Multiple Linear Regression. The data collection techniques used in this study consisted of two stages: conducting library research (studying literature in the form of research journals, scientific papers, articles, and books) and the documentation stage. The results of the study show that (1) Partially, tin price has a positive and significant impact on the stock price of PT Timah Tbk. (2) Partially, variables of interest rate, NPM, and DER have a negative and not significant impact on the stock price of PT Timah Tbk. (2) Simultaneously, tin price, interest rate, NPM, and DER have a significant impact on the stock price of PT Timah Tbk. Keywords : Tin Price, Interest Rate (BI Rate), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Stock Price